Implementasi Sistem Integrasi Repositori Karya Ilmiah di Badan Riset dan Inovasi Nasional (BRIN) Berbasis Eprints - Rahmadani Ningsih Maha; Ayu Retno Widiyaningrum; Tupan Tupan (Media Pustakawan, 2023)
Due to the merging of BATAN, LIPI, BPPT and LAPAN into the National Research and Innovation Agency (BRIN), the repository management in the libraries of those four institutions needs to be integrated. To support the integration, a review of the implementation of the scientific work repository system at the Library of the National Research and Innovation Agency based on Eprints was carried out. The research aims to find out (1) the importance of integrating scientific work repositories in supporting institutions; (2) the benefits of scientific work repository; (3) types of documents in the scientific work repository at BRIN; and (4) a model of scientific work integration system at BRIN. The study was carried out using a descriptive method equipped with a literature study. Data collection was carried out by means of observation and FGD managers of the BRIN scientific work repository. The observation was carried out on September 29, 2022 and the FGD was conducted on November 21, 2022. The results of the study show that an integrated scientific work repository storage system facilitates science and technology human resources in storing scientific work and increases collaboration between BRIN civitas both internally and externally. Scientific work repositories are useful for storing, preserving and increasing the use of research results to increase visibility and research collaboration in order to ensure protection of ownership of scientific work. Repository integration system for scientific papers conducted at BRIN is based on Eprints using the latest version 3.4.3.